Removal of phenol from aqueous solution by dried water hyacinth(Eichhornia Crassipes) - Mohd Hazwan, Mohamad Shayuti (2010)
This potential of dried water hyacinth for phenol adsorption from aqueous solution was studied. The objective in this study is to study the removal of phenol from aqueous solution by dried water hyacinth. Four parameters in this study are effect of initial phenol concentration, dried water hyacinth dosage, pH and contact time. Phenol is very harmful even at low concentration and very hazardous chemical because of their potential toxicity to human health. Adsorption is one of the best methods to remove phenol because of economical and safe process. It is a relatively new process that has been proven very promising in the removal of contaminants from aqueous effluents. Water hyacinth is the suitable adsorbent to remove phenol from aqueous solution. It is very easily available and one of the low cost adsorbent. We used dried to avoid the spreading of dengue fever to the residents nearby and easily to handle and keep it. To conduct this study, first method is collect the water hyacinth. Then, prepare the adsorbent and stock solution. After that, run the experiment for each parameter and lastly analyze the sample. The analysis was done by using UV-Vis Spectrophotometer. From the result obtained, we know that the removal of phenol ions was optimum when initial phenol concentration was almost 70 mg/ L, adsorbent dosage at 1.8 g, pH 3 and at 3 hours contact time. From this study, it is shows that a biomaterial produced from dried water hyacinth can provide a simple, effective and yet cheaper method in removing phenol from aqueous solution.